Learning to succeed : rethinking corporate education in a world of unrelenting change - Wingard, Jason (AMACOM, American Management Association, 2015)
Frequent market shifts ... The rapid pace of technological change ... We're all familiar with the old saying, ""the only constant is change, "" but this has never been as true for business as it is today--nor have the penalties for companies who fail to learn and adapt been as high. Learning to Succeed insists that an integrated model for corporate education--one that links development programs with strategic goals--is critical to building agile and resilient learning organizations that will survive in our fast-evolving business landscape